(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current research aims to reveal the effect of employing the Scamper strategy on the collection of rhetoric and the development of critical thinking among fifth-grade literary students. To achieve the objectives of the research, the researcher applied the experimental approach due to its suitability to the nature of the research, as the researcher chose Tigris Secondary School for Girls in Baghdad Governorate, General Directorate of Education, Al-Karkh, Al-Ghazalia Sector, which included eight preparatory and secondary schools from the fifth literary grade in the Tigris High School for Girls affiliated with the First Karkh Education Directorate (A), the experimental group with 30 students(B) The control group with 31 students. The researcher equivalents the two research groups (experimental and control) in the following variables (age, for female students calculated in months, intelligence, achievement in Arabic for the previous academic year, second course 2021-2022, previous rhetorical information test, tribal critical thinking test). The researcher equivalents the two research groups (experimental and control) in the following variables (age, for female students calculated in months, intelligence, achievement in Arabic for the previous academic year, second course 2021-2022, previous rhetorical information test, tribal critical thinking test). The researcher equivalents the two research groups (experimental and control) in the following variables (age, for female students calculated in months, intelligence, achievement in Arabic for the previous academic year, second course 2021-2022, previous rhetorical information test, tribal critical thinking test). The researcher equivalents the two research groups (experimental and control) in the following variables (age, for female students calculated in months, intelligence, achievement in Arabic for the previous academic year, second course 2021-2022, previous rhetorical information test, tribal critical thinking test). The researcher prepared two tools (the achievement test and the critical thinking test), and with regard to the achievement test, it consisted of 20 items distributed over two questions. The first question included 15 objective items of multiple choice type, and the second question included 5 items from The type of essay questions the critical thinking test may consist of five sub-tests, each of which includes a number of situations, and the validity and stability of the two tools have been verified. The results showed that the performance of the students in the experimental group who studied according to the Scamper strategy was superior to the performance of the students in the control group who studied according to the traditional method of rhetorical achievement. The performance of the students in the experimental group who studied according to the Scamper strategy was superior to the performance of the students in the control group who studied according to the usual method in the critical thinking test. In light of the results, the researcher presented a set of recommendations and suggestions.